Is it too what?

Algebra Level pending

{ ( 1 + x ) ( 1 + y ) = 4 y ( 1 + y ) ( 1 + z ) = 4 z ( 1 + z ) ( 1 + x ) = 4 x \large \begin{cases} (1+x)(1+y)=4y\\ (1+y)(1+z)=4z \\ (1+z)(1+x)=4x \end{cases}

Let x , y x,y and z z be numbers satisfying the equation above, find x + y + z x+y+z .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Ayush G Rai
May 12, 2016

Let x = u + 1 , y = v + 1 x=u+1,y=v+1 and z = w + 1 z=w+1 .From he first equation,we get
( u + 2 ) ( v + 2 ) = 4 ( v + 1 ) (u+2)(v+2)=4(v+1) ;when expand and simplify you get u v = 2 v 2 u . 1 uv=2v-2u.- - - 1
Similarly, v w = 2 w 2 v 2 vw=2w-2v - - - 2
and w u = 2 u 2 w . 3 wu=2u-2w. - - - 3


Hence,
u v w = 2 v w 2 w u uvw=2vw-2wu , [when we multiply the 1st equation by w]
u v w = 2 w u 2 u v uvw=2wu-2uv , [when we multiply the 2nd equation by u]
u v w = 2 u v 2 v w . uvw=2uv-2vw. [when we multiply the 3rd equation by v]

Adding these three relations we get 3 u v w = 0 3uvw=0 .
Suppose u = 0 ; x = u + 1 x = 0 + 1 x = 1 u=0;x=u+1\Rightarrow x=0+1\Rightarrow x=1 .
In the first equation of our problem ( 1 + x ) ( 1 + y ) = 4 y (1+x)(1+y)=4y .
Substitute x = 1 x=1 in the first equation.
We get, ( 1 + 1 ) ( 1 + y ) = 4 y (1+1)(1+y)=4y
( 2 ) ( 1 + y ) = 4 y (2)(1+y)=4y
( 1 + y ) = 2 y (1+y)=2y
y = 1 y=1 .
Again if we substitute y = 1 y=1 in the second equation we get z = 1 z=1 .
So, x + y + z = 1 + 1 + 1 = 3 x+y+z=1+1+1=\boxed 3 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...